2017
DOI: 10.1007/5584_2017_85
|View full text |Cite
|
Sign up to set email alerts
|

Physical Functioning and Symptoms of Chronic Fatigue in Sarcoidosis Patients

Abstract: Scientific reports underscore the importance of measuring the health-related quality of life in sarcoidosis patients. The present study seeks to define how sarcoidosis patients' quality of life, daily physical activity, and physical performance are related to each other. Seventeen patients (mean age 46.8 ± 8.8 years) suffering from sarcoidosis completed the following questionnaires: the fatigue assessment scale (FAS), the quality of life scale (SF-36 questionnaire), and the Borg dyspnea scale. Physical activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
1
14
0
3
Order By: Relevance
“…The results of this study show that DL PA is decreased in adult patients with stage IV sarcoidosis and that SPD is significantly associated with VO 2 max. Our results are in agreement with three previous studies evaluating physical activity in patients with sarcoidosis . Kostorz et al evaluated the comorbidities associated with DL PA in 30 patients with sarcoidosis, albeit without precise radiological staging and found that the patients had walked a mean (±SD) SPD of 5214 (±2699).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of this study show that DL PA is decreased in adult patients with stage IV sarcoidosis and that SPD is significantly associated with VO 2 max. Our results are in agreement with three previous studies evaluating physical activity in patients with sarcoidosis . Kostorz et al evaluated the comorbidities associated with DL PA in 30 patients with sarcoidosis, albeit without precise radiological staging and found that the patients had walked a mean (±SD) SPD of 5214 (±2699).…”
Section: Discussionsupporting
confidence: 92%
“…Kostorz et al evaluated the comorbidities associated with DL PA in 30 patients with sarcoidosis, albeit without precise radiological staging and found that the patients had walked a mean (±SD) SPD of 5214 (±2699). Pilzak et al found that patients with sarcoidosis not only showed low mean SPD (4566 ± 2378) but also displayed reduced exercise tolerance, as measured by the VO 2 max and 6MWT . However, that study did not examine correlations between DL PA and pulmonary function, exercise tolerance, or mood parameters (anxiety and depression).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…While activity tracking at home could possibly help to stimulate exercise [51,[53][54][55], supervised training programs or multidisciplinary pulmonary rehabilitation might have more beneficial effects [13]. Current evidence indicates that a structured, supervised exercise program can improve symptoms, QoL, exercise capacity, and muscle strength in patients with different stages of sarcoidosis [56][57][58][59][60][61].…”
Section: Backingmentioning
confidence: 99%
“…Inspiratory muscle impairment, 70,161 extremity muscle weakness, 81 reduced 6MWD, 72,81,84,207 and reduced exercise capacity 72,81 have been associated with lower HRQoL in sarcoidosis patients. The relationship between HRQoL and pulmonary function in sarcoidosis has been contradictory.…”
Section: Physiologic Parameters and Hrqolmentioning
confidence: 99%